2010
DOI: 10.1016/j.jcm.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intraexaminer reliability of the Blair protractoview method: examination of a chiropractic radiographic technique

Abstract: Objective: The purpose of this study was to evaluate the inter-and intraexaminer reliability of the Blair protractoview radiographic method. Methods: This retrospective study evaluated 25 participants attending a Blair technique seminar. Participants included chiropractic students and doctors of chiropractic with more than 11 years of experience. Participants evaluated 100 Blair protractoview radiographs (oblique nasium). A κ analysis was used to determine the inter-and intraexaminer reliability because of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Film selection for this study may not reflect clinical practice since doctors in practice do not get to actively select films based on quality or anatomical anomalies. 1 , 4 This study used a convenience sample of radiographs with optimized quality intended to reduce variability, and all radiographs used were of acceptable quality for NUCCA board-certification films. Thus, this controlled environment does not necessarily reflect actual practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Film selection for this study may not reflect clinical practice since doctors in practice do not get to actively select films based on quality or anatomical anomalies. 1 , 4 This study used a convenience sample of radiographs with optimized quality intended to reduce variability, and all radiographs used were of acceptable quality for NUCCA board-certification films. Thus, this controlled environment does not necessarily reflect actual practice.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could consider using a random sample of films or consecutive films, a larger and random sample of NUCCA-certified doctor-examiners, and films showing no misalignment as a control group, and they could allow examiners to review the acceptability of film sets used in the study, as suggested by Hubbard. 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiographic series is taken to view the cervical articulations, giving the doctor an opportunity to visualize the state of potential juxtaposition of each cervical articulation. 10,28 This method of radiographic analysis is thought to eliminate the inherent error that may occur with line analysis techniques due to spinal asymmetry (Figs 3 and 4).…”
Section: Discussionmentioning
confidence: 99%